(untitled) (International Journal of Engineering and Computer Science, 2014)
Internet crime is crime committed on the Internet, using the Internet and by means of the Internet”.Since the introduction of the Internet in the 1950’s, the world has been introduced to innovative technology that has seemingly enhanced our lives. It has brought convenience to the busy lifestyle. However, this continuum of boundless information has become a portal for Internet criminals to breach the barriers of online privacy and protection. Internet crimes (also termed as ‘computer’ or ‘web’ or ‘cyber’ crimes) are being viewed as one of the greatest challenges of the 21st century. From child pornography and sex crimes to Internet theft and computer fraud, prosecutors and investigators are aggressively confronting all types of computer and web crime.